Specificity of Formation of Complexes Between Coat Protein and Bacteriophage f2 RNA - Chroboczek, Jadwiga (1973)
The specificity of formation of phage f2 RNA-protein complexes was studied. Complex I contains up to 8 mol of coat protein per 1 mol of RNA. Its formation proceeds equally well in medium (i) without magnesium ions, (ii) containing magnesium ions, (iii) containing 4 mM EDTA, and (iv) at temperatures from 0 to 45 C. Complex II contains up to 200 mol of coat protein per 1 mol of RNA. Its formation is inhibited by the presence of magnesium ions in medium. Formaldehyde- or methoxyamine-treated f2 RNA in which only exposed bases were modified showed a normal pattern of complex II formation, whereas formation of complex I was inhibited or abolished. We conclude that complex I formation involves the interaction between coat protein and specific region of exposed bases in RNA. A possible site of attachment of coat protein is discussed.